Dataset for Natural and anthropogenic controls on wood loads in river corridors of the Rocky, Cascade, and Olympic mountains, USA - Scott, Daniel; Wohl, Ellen (Colorado State University. Libraries, 2018)
This dataset describes wood loads in four mountain river basins of the Western United States. In addition to wood load, this dataset includes valley bottom, topographic, and forest characteristics. Please see the accompanying article (DOI listed upon publication) for a full explanation of methods used to collect this data and resulting analysis.
Department of Geosciences
Keywords: wood; river; geomorphology